The role of the basolateral amygdala in dreaming. (April 2019) - Blake, Yvonne; Terburg, David; Balchin, Ross; van Honk, Jack; Solms, Mark
Abstract: Neuroimaging studies have repeatedly shown amygdala activity during sleep (REM and NREM). Consequently, various theorists propose central roles for the amygdala in dreaming – particularly in the generation of dream affects, which seem to play a major role in dream plots. However, a causal role for the amygdala in dream phenomena has never been demonstrated. The traditional first step in determining this role is to observe the functional effects of isolated lesions to the brain structure in question. However, circumscribed bilateral amygdala lesions are extremely rare. Furthermore, the treatment of the amygdala as a unitary structure is problematic, as the basolateral and centromedial amygdala (BLA and CMA) may serve very different functions. We analysed 23 dream reports collected from eight adult patients with bilateral calcification of the BLA as a result of a very rare genetic condition called Urbach-Wiethe Disease (UWD). We compared these dream reports to 52 reports collected from 17 matched controls. Given that the BLA has been implicated in various affective processes in waking life, we predicted that the emotional content of the patients' dreams would differ from that of controls. Due to the exploratory nature of this research, a range of different dream characteristics were analysed. A principal components analysis run on all data returned three key factors, namely pleasantness, length and danger . The UWD patients' dream reports were significantly more pleasant and significantly shorter and less complex than control reports. No differences were found in levels of threat or danger. The results support some current hypotheses concerning the amygdala's role in dreaming, and call others into question. Future research should examine whether these UWD patients show generally impaired emotional episodic memory due to BLA damage, which could explain some of the current findings.